CORPORATE CULTURE MODEL SEBAGAI ALASAN PENGHAPUS PIDANA KORPORASI: JUSTIFIKASI TEORITIS PEMIDANAAN KORPORASI DALAM KUHP - Brouwer, Darryl Evan (Faculty of Law, Universitas Tanjungpura, 2025)
AbstractLaw Number 1 of 2023 concerning the Criminal Code has accommodated corporations as perpetrators of criminal acts as well as natural humans. With distinct characteristics to natural humans, the attribution of corporate criminal responsibility to corporations is also distinct to natural humans. The Criminal Code stipulates the attribution of corporate blameworthiness, one of which is the corporate culture model theory, but not as a reason for corporate